Effect of Drought and Seasons on Performance and Stability of Maize Genotypes - Kumar, P; Godawat, S L; Pandiya, N K; Vyas, Mukesh (Annals of Arid Zone, 2016)
Twenty single cross hybrids developed by crossing ten elite inbred lines with two drought tolerant exotic testers (viz. CML-341 and Pool 16 BN) in line x tester mating design, were evaluated along with parental lines and three checks under rainfed (during kharif 2004), normal inigation and terminal drought (during rabi 2004-05). Hybrids (F'ls) exhibiled higher grain yield, plant height and ear length along with reduced ASI and earliness over parental lines under all the environments, indicated that hybrids had better growth and vigor as compared to their inbred parental lines. Traits under investigation were controlled by both additive Â«j2 A) and non-additive Â«j2 D) gene actions and thus could be improved through selection followed by hybridization. The parental line Pool 16 BN was found to be stable for grain yield and anthesis-silking interval (ASI), while inbred EI-573 was better under water stress environment. Hybrid (EI-569 x CML-34I) was stable for grain yield and found suitable under moisture stress environment for AS!. The early hybrids (EI-572 x Pool 16 BN) and (EI-571 x P~ol 16 BN) found suitable under high yielding environments for grain yield, while for ASI these hybrids were suitable under favorable and unfavorable environments, respectively. Navjot was also found appropriate under moisture stress environments. Key words: Exotic tester, terminal drought, genotype, genotype x environment interaction.